ELDEST DAUGHTER SYNDROME: KONSTRUKSI SOSIAL, BIAS GENDER, DAN PEMBENTUKAN BEBAN PERAN ANAK PEREMPUAN PERTAMA DALAM KELUARGA - Alifa Izzatun Nisa; Wilodati; Puspita Wulandari (Jurnal Sosiologi UPR, 2026)
The phenomenon of Eldest Daughter Syndrome is increasingly discussed on social media, particularly on the X platform, where posts highlight the excessive burden placed on the eldest daughter. Complaints regarding domestic demands, high expectations to set a good example for younger siblings, caregiving roles, and emotional pressure indicate that this condition is not merely an individual issue but part of a social construct shaped by family socialisation patterns. This study aims to analyse how family socialisation, gender norms, and role expectations contribute to the emergence of the Eldest Daughter Syndrome. The research employs a qualitative approach, using data from social media posts. Analysis is conducted using thematic analysis to identify narrative patterns related to the division of roles within the family and gender bias. The findings indicate that the role of the eldest daughter is shaped through a socialisation process that places an unequal burden of responsibility upon her, making her vulnerable to role conflict, feelings of guilt when prioritising her own needs, stress, and emotional exhaustion. This study underscores the importance of family awareness in restructuring role divisions to ensure a fairer distribution, thereby preventing the repeated pressure on the eldest daughter.